Teacher perceptions of training and intention to use robotics - Santos, I.; Ali, N.; Khine, Myint Swe; Hill, A.; Abdelghani, U.; Qahtani, K. (2016)
© 2016 IEEE. This paper presents an overview of a work in progress research project that investigated cycle 2 in-service teachers' perceptions of the effectiveness of a training offered in the United Arab Emirates on how to use and integrate robotics in teaching. The project also investigated teacher beliefs, attitudes and intention to use robotics in their future teaching. A description of the training offered to cycle 2 teachers is presented. Potential contributions to the context and knowledge as well as future work are discussed.